Migration and wage inequality: a~detailed analysis for German metropolitan and non-metropolitan regions - Ramona Schmid (Review of Regional Research, 2023)
This study presents new evidence on immigrant-native wage gaps considering regional-specific differences between 2000 and 2019 in Germany. Using linked employer-employee-data, unconditional quantile regression models are estimated in order to assess the degree of labor market integration of foreign workers. The applied extended version of the Oaxaca-Blinder decomposition method provides evidence on driving factors behind wage gaps along the entire wage distribution. Estimated results are presented not only for the whole of West Germany but also differentiated between metropolitan and non-metropolitan areas. On average, larger wage differentials are identified in metropolitan areas with at the same time a~higher presence of foreign population. Detailed decompositions show that there are not only changes in the relative importance of explanatory factors over time, but also possible sources of wage differentials shift between different points of the wage distribution. Decisive explanatory variables in this context are the practised profession and the economic sector affiliation. Distinguishing between metropolitan and non-metropolitan areas, provides evidence that especially differences in educational attainment impact wage gaps in urban areas. Regarding the size of overall estimated wage gaps, after 2012 a~reversal in trend and particular increasing tendencies around median wages are revealed.
Keywords: J15; J31; J61; R23; R58; 910; Immigrant-native wage gap; Oaxaca-Blinder decomposition; Unconditional quantile regression; Ethnic clustering; Germany; Lohngefälle zwischen Einheimischen und Zuwanderern; Oaxaca-Blinder Zerlegung; Unbedingte Quantilsregression; Ethnische Gruppierung; Deutschland